Concept of Marriage of Choice in Islam: An Academic Study: اسلام میں پسند کی شادی کا تصور: ایک علمی مطالعہ - Naseer, Muhammad; Ibrahim, Dr. Muhammad; Kiran, Sana (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The Islamic framework for marriage represents a structured institution that serves as the cornerstone of human society. When this system operates seamlessly, it safeguards the community from social corruption and instability. Conversely, any disruption within this framework can lead to widespread societal challenges. To address these concerns, Islamic teachings provide a comprehensive and systematic approach to marriage, offering solutions to many contemporary issues that may otherwise appear unresolved. Islam emphasizes the sanctity of the marital relationship by granting it legal and moral recognition, positioning it as a fundamental societal value. Through the institution of marriage, specific guidelines are prescribed to strengthen this bond and achieve its core objectives, while discouraging excessive and unnecessary emotional indulgence. The Qur’an and Hadith underscore the importance of fostering a morally upright society by advocating chastity and legitimizing intimate relationships within the bounds of marriage. This approach not only fulfills the human need for sexual fulfillment but also ensures the protection of lineage and the continuation of life, thereby contributing to societal stability and harmony.